Analisis Rasio Likuiditas Dan Rasio Profitabilitas dalam Mengukur Kinerja Keuangan Pada Koperasi Cahaya Phinisi Nusantara - Mardiana Ibrahim; Andi Bintang Balele; Arman K. (Universitas 17 Agustus 1945 Semarang, 2022)
The activities of the Cahaya Phinisi Nusantara PT Bank Sulselbar cooperative can be measured based on the cooperative's financial performance. The good and bad financial performance of a cooperative can be assessed through financial reports in the form of a balance sheet or cooperative profit and loss report which is presented regularly. The aim of this research is to obtain an in-depth overview of Liquidity Ratio Analysis and Profitability Ratios in measuring financial performance in cooperatives. The research approach used is quantitative research with a descriptive approach. The descriptive method is a method used to collect, classify, analyze and interpret data related to the problem and compare it with the actual situation at the Cahaya Phinisi Nusantara Cooperative PT Bank Sulselbar and then draw conclusions. Analysis of Profitability Ratios at the Cahaya Phinisi Nusantara Cooperative PT. Bank Sulselbar in terms of the average value of Return On Assets (ROA) of four point forty three percent (4.43%) and Return On Equity (ROE) of five point eighty six percent ( 5.86%) where the value of the benchmark and determining the cooperative health predicate is five percent (5%) which indicates that it is not good at optimizing its own capital and investment in generating net profits.